2017
DOI: 10.15406/mojs.2017.05.00105
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Case of Pruritus Vulvae (Prurigo Nodularis): A Rare Case Report

Abstract: Prurigo Nodularis, an unusual disorder with unknown aetiology, notoriously resistant to therapy is characterized by extremely pruritic nodules with well-defined clinical symptoms and histopathological findings. Herein, we report a case of a 19-year-old female student presenting with complaint of pruritis vulvae for 3years. She took treatment off and on in the form of topical and systemic antibiotics, anti fungal, anti-histaminics and steroids, but was not relieved. Vulval biopsy was done and histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In 2017, Akhtar et al reported a case of a 19-year-old female with pruritus vulvae for three years that was resistant to treatment. Physical examination showed a dry patch measuring 0.5 x 1 cm on her vulva and a biopsy revealed PN [ 8 ]. Despite a few reported cases of unique presentations of PN, our case is the first reported case of PN with limited involvement over the acral areas only.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Akhtar et al reported a case of a 19-year-old female with pruritus vulvae for three years that was resistant to treatment. Physical examination showed a dry patch measuring 0.5 x 1 cm on her vulva and a biopsy revealed PN [ 8 ]. Despite a few reported cases of unique presentations of PN, our case is the first reported case of PN with limited involvement over the acral areas only.…”
Section: Discussionmentioning
confidence: 99%